Association between IgG responses against the nucleocapsid proteins of alphacoronaviruses and COVID-19 severity - Nückel, Julius; Planatscher, Elisa; Mohr, Anne Wiebe; Deichl, Karolin; Mijočević, Hrvoje; Feuerherd, Martin; Wolff, Lisa; Erber, Johanna; Schneider, Jochen; Quante, Michael; Winter, Christoph; Ruland, Jürgen; et al. (Frontiers in Immunology, 2022)
Understanding immune responses to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is crucial to contain the COVID-19 pandemic. Using a multiplex approach, serum IgG responses against the whole SARS-CoV-2 proteome and the nucleocapsid proteins of endemic human coronaviruses (HCoVs) were measured in SARS-CoV-2-infected donors and healthy controls. COVID-19 severity strongly correlated with IgG responses against the nucleocapsid (N) of SARS-CoV-2 and possibly with the number of viral antigens targeted. Furthermore, a strong correlation between COVID-19 severity and serum responses against N of endemic alpha- but not betacoronaviruses was detected. This correlation was neither caused by cross-reactivity of antibodies, nor by a general boosting effect of SARS-CoV-2 infection on pre-existing humoral immunity. These findings raise the prospect of a potential disease progression marker for COVID-19 severity that allows for early stratification of infected individuals.